A Minimal Protocol for Right Relations: Reframing the Critique of Anthropocentrism Through Responsibility, Vulnerability, and Public Anchors - Choi Yongho (Philosophy & Social Criticism, 2026)
This paper treats anthropocentrism as a relational standing-order rather than only as a claim about intrinsic value. Anthropocentric arrangements give default priority to human convenience and self-image while shifting vulnerability and accountability costs elsewhere. The argument integrates moral deskilling, responsibility-gap analysis, relational standing, and vulnerability-first reasoning to explain a recurring pattern across nonhuman animals, environmental relations, and AI-mediated systems. Distorted relations damage intellectual capacities of understanding, judgment, and verification; emotional capacities of empathy, aversion, and attachment; and volitional capacities of commitment, responsibility-taking, and self-control. I analyze relational breakdown through instrumentalization, miscalibrated social response, responsibility diffusion, and attentional or empathic pollution. AI serves as an amplifier case because conversational, recommender, and automation systems can make these elements visible at scale. The paper proposes a minimal protocol: responsibility ownership, vulnerability-first attention, public anchors of traceability, contestability, and corrigibility, and capacity preservation.